2005
DOI: 10.1017/s0025315405011781
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic distinction of Ophelia barquii and O. bicornis (Annelida: Polychaeta) in the Mediterranean as revealed by ISSR markers and the number of nephridiopores

Abstract: Ophelia bicornis sensu lato is a polychaete living in intertidal sandy habitats of Mediterranean and European Atlantic coasts, whose systematics have been strongly debated in the past few decades. In the present work the count of nephridiopores was coupled with genetic analysis carried out with DNA markers (inter simple sequence repeats) for a total of 30 individuals collected at six Italian beaches. Exact test, analysis of molecular variance, non-metric multidimensional scaling and assignment tests clearly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…The amplified DNA fragment lengths (for all primers) were approximately from 247 to 1922 pb. Maltagliati et al (2005) defined a locus as ''fully diagnostic'' when it produced bands in all individuals of one species and not in the other, and ''nearly diagnostic'' when it pro- duced species-specific bands in some individuals (but not all) of one species and not in the other species. We detected 2 fully diagnostic and 9 nearly diagnostic loci in the presumed species S. blainvillei and only 6 nearly diagnostic loci in the second species S. megalops.…”
Section: Issr Methodsmentioning
confidence: 99%
“…The amplified DNA fragment lengths (for all primers) were approximately from 247 to 1922 pb. Maltagliati et al (2005) defined a locus as ''fully diagnostic'' when it produced bands in all individuals of one species and not in the other, and ''nearly diagnostic'' when it pro- duced species-specific bands in some individuals (but not all) of one species and not in the other species. We detected 2 fully diagnostic and 9 nearly diagnostic loci in the presumed species S. blainvillei and only 6 nearly diagnostic loci in the second species S. megalops.…”
Section: Issr Methodsmentioning
confidence: 99%
“…In this context, results from our ISSR survey may add a further line of evidence to the presence of cryptic species in Hediste diversicolor. Previous researches showed that these markers are able to discriminate with accuracy closely related species of polychaetes (Maltagliati et al 2005), cyprinodontiform fishes (Maltagliati et al 2006b), and proseriate flatworms (Casu et al 2009). Interestingly, Bayesian clustering may be successful in species' delimitation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…ISSR molecular markers have been proven to be useful in studying inter-and intraspecific relationships (Casu et al 2005, Maltagliati et al 2005, 2006b, Varela et al 2007, De Aranzamendi et al 2008, Lai et al 2008, Pannacciulli et al 2009). Although ISSRs are dominant markers, simulation studies indicated that this kind of markers may be as efficient as codominant ones in estimating genetic diversity if an appropriate number of loci is used (Mariette et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bellan 1964a) who considered Ophelia radiata barquii and Ophelia radiata synonyms of Ophelia bicornis. However, molecular and morphological analyses by Maltagliati et al (2004) and Maltagliati et al (2005) Notes: Species complex with a confused taxonomic history. Originally described from the Gulf of Naples.…”
Section: Ophelia Barquii Fauvel 1927mentioning
confidence: 99%
“…However, they were not able to assign Mediterranean specimens to either of the two Atlantic forms. Maltagliati et al (2005) consider the results inconclusive and refer to the complex as Ophelia bicornis sensu lato. Parapar (2012) studied individuals of both Ophelia radiata and Ophelia bicornis from the collections of the Natural History Museums in Copenhagen and Madrid and could not find any differences apart from the number of gill pairs -a character which he considered too unreliable for discrimination.…”
Section: Ophelia Barquii Fauvel 1927mentioning
confidence: 99%